External determinants of adolescent sexual behavior among Islamic Boarding School Students in Bali - Feni Sulistyawati; Rury Narulita Sari; Ni Putu Widarini; Ni Putu Shinta Utari Dewi; Abdul Hakim (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2026)
Background: Risky sexual behavior among adolescents is a significant concern for sexual health, even in religious settings such as Islamic boarding schools. Although these institutions provide intensive religious education, students remain exposed to external influences that can shape their sexual behavior. Understanding these external determinants is crucial to addressing sexual risk and promoting the psychosocial well-being of adolescents in pesantren environments. Objectives: To analyze the influence of external factors including parental supervision, peer influence, and access to information on adolescent sexual behavior in Islamic boarding schools in Bali. Methods: This study used a quantitative design with a cross-sectional approach. A total of 127 students with varying lengths of stay in Islamic boarding schools and ages ranging from 15-19 years from two Islamic boarding schools in Bali were selected using a total sampling technique. Data were collected using a structured questionnaire that had been tested for validity and reliability. The variables used in this study include independent variables, namely external factors consisting of access to information, parental supervision, and peer influence. The independent variable is sexual behavior with three categories: normal, moderate, and severe. Data analysis was carried out using frequency distribution, crosstabulation, and multinomial logistic regression with the non-risk category as a comparison. Results: Access to information and peer influence have a significant effect on severe risky sexual behavior with a p value <0.05. Adolescents with negative access to information were 6.7 times more likely (OR=6.711; 95% CI=1.797-25.065) to engage in high-risk sexual behavior, while those with negative peer influence were 14.8 times more likely (OR=14.838; 95% CI=1.238-177.883). Conclusions: Access to information and peer influence are the main determinants of high-risk sexual behavior among adolescents in Islamic boarding schools in Bali. Prevention efforts need to be directed at strengthening appropriate literacy and establishing peer educators.